Biopolitical Theory of Virtuosity in the Oeuvre of Glenn Gould - Rodić, Bojana (AM Journal of Art and Media Studies, 2021)
Over the course of the 20th century, the concept of virtuosity went through a transformation and adapted to its increasingly globalized and technological culture. In that sense, virtuosic performance and its reception were subject to the workings of social, political, economic, and historical factors. The emergence of a media-networked society conditioned a change in the perception of the artist, who now creates and transmits her works using media. Contemplating the concept of virtuosity in the age of post-Fordism, originally posited in the bio-political theory of the Italian philosopher Paolo Virno, this text analyses the concepts of the general intellect, labor power, as well as public political performance. Its focus is on the creative oeuvre of Glenn Gould, whose work combined different layers of pianist and performance heritage, and offered a new type of interpretation. Harnessing the power of his idea, he succeeded in using his radical musical philosophy to re-examine virtuosic performance and create a hybrid art as a blend of music and technology. In Gould’s poetics, virtuosity was a skill that managed to transpose itself into the domain of media by building upon preceding discursivizations. Article received: April 18, 2020; Article accepted: July 1, 2020; Published online: April 15, 2021; Original scholarly paper